2000
DOI: 10.1007/s002280050726
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and pharmacodynamics of propofol 6% SAZN versus propofol 1% SAZN and Diprivan-10 for short-term sedation following coronary artery bypass surgery

Abstract: The pharmacokinetics, pharmacodynamics and safety characteristics of propofol 6% SAZN are in good agreement with those of the 1% formulations. Propofol 6% SAZN therefore provides a useful alternative to the commercially available 1% formulation for short-term sedation in the intensive care unit. Expected advantages in long-term sedation of the 6% over 1% formulation are the subject of an ongoing study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 17 publications
2
22
0
1
Order By: Relevance
“…Other recent studies did not find any effect of the changing formulation on the pharmacokinetics or pharmacodynamics of propofol. [9][10][11][12] In the current study, the commercially available propofol formulation, Diprivan 2%, was compared to the newly formulated propofol 2% for bioequivalence with regard to pharmacokinetic parameters after each study drug was administered as a single 2-mg/kg bolus dose. The 90% confidence interval for the AUC ratio was included by the acceptance range for bioequivalence (80%-125%).…”
Section: Discussionmentioning
confidence: 99%
“…Other recent studies did not find any effect of the changing formulation on the pharmacokinetics or pharmacodynamics of propofol. [9][10][11][12] In the current study, the commercially available propofol formulation, Diprivan 2%, was compared to the newly formulated propofol 2% for bioequivalence with regard to pharmacokinetic parameters after each study drug was administered as a single 2-mg/kg bolus dose. The 90% confidence interval for the AUC ratio was included by the acceptance range for bioequivalence (80%-125%).…”
Section: Discussionmentioning
confidence: 99%
“…[6] In another study, propofol formulation 6% in Lipofundin MCT/LCT 10% had a similar incidence of pain on injection as LCT propofol containing intralipid 10%. [7] Lipofundin MCT/LCT 10% is a 10% fat emulsion consisting of MCT and LCT, whereas intralipid 10% contains only LCT. [7] In several other studies, less pain is reported with MCT/LCT preparation compared to LCT preparation.…”
Section: Different Formulations Of Propofolmentioning
confidence: 99%
“…[7] Lipofundin MCT/LCT 10% is a 10% fat emulsion consisting of MCT and LCT, whereas intralipid 10% contains only LCT. [7] In several other studies, less pain is reported with MCT/LCT preparation compared to LCT preparation.…”
Section: Different Formulations Of Propofolmentioning
confidence: 99%
“…5,6 For this reason, a new formulation, propofol 6%, has been developed, resulting in a reduction of fat, emulsifier, and volume load by 83%. Propofol 6% has previously been studied for short-term use in clinical 11,12 and preclinical 13 studies.…”
mentioning
confidence: 99%